Phase I study of evofosfamide, an investigational hypoxia‐activated prodrug, in patients with advanced leukemia. Issue 8 (25th June 2016) - Badar, Talha; Handisides, Damian R.; Benito, Juliana M.; Richie, Mary Ann; Borthakur, Gautam; Jabbour, Elias; Harutyunyan, Karine; Konoplev, Sergej; Faderl, Stefan; Kroll, Stew; Andreeff, Michael; Pearce, Tillman; et al.
Abstract : Tumor hypoxia causes resistance to radiation and chemotherapy. Evofosfamide (TH‐302) has exhibited specific hypoxia‐dependent cytotoxicity against primary acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) samples in vitro. Based on these findings, a Phase I study of evofosfamide was designed for patients with relapsed/refractory leukemia (NCT01149915). In this open‐label study, patients were treated with evofosfamide as a 30–60 min/day infusion on Days 1–5 of a 21–day cycle (Arm A, n  = 38) or as a continuous infusion over 120 hr over Days 1–5 of a 21‐day cycle (Arm B, n  = 11). Forty‐nine patients were treated including 39 (80%) with AML and 9 (18%) with ALL. Patients had received a median of five prior therapies. In Arm A, the dose‐limiting toxicities (DLTs) were grade 3 esophagitis, observed at a dose of 550 mg/m 2 . The maximum tolerated dose (MTD) was a daily dose of 460 mg/m 2 . In Arm B, the DLTs were grade 3 stomatitis and hyperbilirubinemia, observed at a daily dose of 460 mg/m 2 . The continuous infusion MTD was a daily dose of 330 mg/m 2 . Hypoxia markers HIF‐1α and CAIX were highly expressed in leukemic bone marrow and were significantly reduced after evofosfamide therapy. The combined overall response rate in Arms A and B was 6% (2 CR/CRi and 1 PR), with all responses seen in Arm A. Evofosfamide has shown limited activity in heavily pretreated leukemia patients. Further evaluation investigating evofosfamide in combination with cytotoxic or demethylating agents is warranted. Am. J. Hematol. 91:800–805, 2016. © 2016 Wiley Periodicals, Inc.